Effects of low-serum adaptation on growth and protein expression in stably lactoferrin-overexpressing mammary alveolar cells - Qiang, Zhenxing; Cai, Xiaoqian; Zhang, Zhenzhen; Wang, Hui; Wang, Qiuying; Ji, Yajing; Li, Guangpeng; Su, Guanghua; Yang, Lei; Qiao, Weicang; Zhao, Junying; Chen, Ming; et al. (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveLong-term culture with high serum concentrations increases culture costs, accelerates cell senescence, and limits industrial-scale applications. Serum reduction adaptation is an effective solution for addressing these issues. In this study, we aimed to investigate the effects of two low-serum adaptation strategies on the growth and lactoferrin expression in stably LTF-overexpressing bovine mammary alveolar cells transfected with large T antigen (MAC-T).MethodsTwo adaptation protocols of serum concentration reduction and dual-medium gradient adaptation were implemented to progressively reduce serum dependence in MAC-T cells.ResultsUnder both adaptation modes, cells maintained stable proliferation at 1% fetal bovine serum (FBS). At the 0.5% FBS (serum reduction) and 10% basal control medium, equivalent to 1% FBS in dual-medium adaptation stages, adding 10% knockout™ serum replacement and 1% insulin-transferrin-selenium 5 increased the specific growth rate by 30%, enabling robust cell growth under low-serum conditions.ConclusionAcross all the low-serum conditions, cells retained typical epithelial morphology (cytokeratin 18-positive) while exhibiting consistent LTF mRNA transcription levels, protein expression, and secretory output. These findings validate the scalable low-serum culturing of MAC-T cells and in vitro LTF synthesis.